Biochemical and biophysical analysis of two Antarctic lysozyme endolysins and in silico exploration of glycoside hydrolase 19 sequence space - ORLANDO, MARCO (Università degli Studi di Milano-Bicocca, 2020)
Biodiversity of organisms and their genomic content is a valuable source of enzymes, some of which can be isolated and turned into biocatalysts, useful for more sustainable and efficient industrial processes. Organisms thriving in constantly cold environments produce enzymes that may be more efficient in the cold and more thermolabile than enzymes from other organisms, and that display interesting features for the catalysis of several processes that require or are better at low temperature. In the first part of this thesis, two glycoside hydrolases of family 19 (GH19), named LYS177 and LYS188, were identified in the genome of an Antarctic Pseudomonas strain and characterized. Even though most of the characterized GH19 are chitinases, LYS177 and LYS188 showed no chitinolytic activity, but were active as lysozymes with an optimum temperature of 25-35°C, and retained 40% of their highest activity at 5°C. The temperatures of midpoint unfolding transition were estimated to be 20°C higher than their optimum of activity. Based on these features and sequence analysis, LYS177 and LYS188 can be considered cold-active phage endolysins integrated in prophagic regions of the bacterial host. Moreover, the best performing of the two, LYS177, was active and structurally stable over several days only at 4°C, indicating it as a candidate for potential application on the preservation of food and beverages during cold storage. In protein families, enzymes can rapidly acquire new specializations. Therefore, best practices should be implemented to select optimal candidates with the activity of interest and new, potentially promising, features. Characterized GH19 enzymes showed an enhanced in vivo crop defence against chitin containing pathogens and antimicrobial potentialities. In the second part of this thesis, the sequence space of the GH19 family was explored and a database was created to highlight non-described sequences potentially endowed with interesting variants. Based on global pairwise sequence identity of all proteins ...